From Guatemala to the Internal Provinces of the West. Provincial Councils and Fiscal Structure and Constitutional Councils´ Public Finances, 1820-1822 - Serrano Ortega, José Antonio (2021)
This brief article analyzes the fiscal measures that provincial councils and political bosses implemented in initial efforts to contain the “territorial revolution of towns”. The starting point of this process consisted in imposing control on the public treasuries of the constitutional governments. The years 1820-1822 marked the beginnings of the processes that would frame the histories of political transitions in the various regions of Mexico and Central America in the first half of the 19th century. The article shows that while the constitutional governments and provincial councils established from Guatemala all the way to the Internal Provinces of Western Mexico played key roles in that period of profound change, the conclusion is that elected officials (diputados) forged alliances with disparate political groups that allowed these institutions of provincial government to impose political and administrative control on constitutional governments.